2006
DOI: 10.1530/eje.1.02291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modest testosterone supplementation and exercise for 12 weeks on body composition and quality of life in elderly men

Abstract: Objective: One of the factors that may promote deterioration in quality of life and body composition in elderly men is the relative decline in serum testosterone levels with aging. In this study, we assessed the effects of modest doses of testosterone and a home-based strengthening program on quality of life and body composition in elderly men with relative testosterone insufficiency. Design: Double-blind, placebo-controlled randomized study (testosterone), and additional randomization to a resistance exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 44 publications
2
37
0
2
Order By: Relevance
“…The same variation in waist circumference was demonstrated by our group in postmenopausal women, at the beginning of hormone replacement therapy (35). With regard to waist-to-hip ratio, some studies have shown that testosterone replacement rapidly improved this ratio, particularly when associated with regular physical exercise (36), thus representing an important parameter for metabolic syndrome improvement.…”
Section: Discussionsupporting
confidence: 79%
“…The same variation in waist circumference was demonstrated by our group in postmenopausal women, at the beginning of hormone replacement therapy (35). With regard to waist-to-hip ratio, some studies have shown that testosterone replacement rapidly improved this ratio, particularly when associated with regular physical exercise (36), thus representing an important parameter for metabolic syndrome improvement.…”
Section: Discussionsupporting
confidence: 79%
“…19 The conflicting results are mainly due to small sample size [36][37][38][39][40][41][42] and recruiting men solely based on serum testosterone level. 35,38,[42][43][44][45] Haren et al…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown beneficial effects of oral TU on men with TDS using disease-specific QoL scales. 50,51 However, studies using generic SF-36 QoL scales that recruited men based on the criterion of low serum testosterone level alone had either shown improvement in the physical components of QoL scales 35,44 or no effect in any of the components. 38,42,43,45 The lack of improvement seen was because the participants in these studies might not have TDS, as having a low serum TT alone does not fulfill the diagnosis of TDS.…”
mentioning
confidence: 99%
“…A administração de dehidroepiandrosterona (DHEA) 50 mg, 2 vezes ao dia, pode ser feita, contudo não há estudos que documentem sua eficácia. Ainda como medicamento oral, mucoadesivos bucais com 30mg tem tido eficácia em melhorar os níveis de testosterona em pacientes hipogonádicos [100][101][102] . Outra forma de administração de testosterona é a utilização de adesivos transdérmicos.…”
Section: ) Terapia Hormonalunclassified
“…Os adesivos escrotais liberam de 4 a 6 mg/dia de testosterona e são melhor absorvidos que os não-escrotais. Em pacientes com DAEM, os adesivos transdérmicos são bem aceitos na dose de 5 a 7,5 mg/dia e trocados a cada 48 horas [100][101][102] . Os adesivos não-escrotais liberam 5 mg/dia de testosterona e devem ser aplicados em pele glabra, seca e limpa.…”
Section: ) Terapia Hormonalunclassified